Analysis of Inactivation of SARS-CoV-2 by Specimen Transport Media, Nucleic Acid Extraction Reagents, Detergents, and Fixatives - Welch, Stephen R.; Davies, Katherine A.; Buczkowski, Hubert; Hettiarachchi, Nipunadi; Green, Nicole; Arnold, Ulrike; Jones, Matthew; Hannah, Matthew J.; Evans, Reah; Burton, Christopher; Burton, Jane E.; Guiver, Malcolm; et al. (Journal of clinical microbiology, 2020)
The COVID-19 pandemic has necessitated a multifaceted rapid response by the scientific community, bringing researchers, health officials, and industry together to address the ongoing public health emergency. To meet this challenge, participants need an informed approach for working safely with the etiological agent, the novel human coronavirus SARS-CoV-2. Work with infectious SARS-CoV-2 is currently restricted to high-containment laboratories, but material can be handled at a lower containment level after inactivation. The COVID-19 pandemic has necessitated a multifaceted rapid response by the scientific community, bringing researchers, health officials, and industry together to address the ongoing public health emergency. To meet this challenge, participants need an informed approach for working safely with the etiological agent, the novel human coronavirus SARS-CoV-2. Work with infectious SARS-CoV-2 is currently restricted to high-containment laboratories, but material can be handled at a lower containment level after inactivation. Given the wide array of inactivation reagents that are being used in laboratories during this pandemic, it is vital that their effectiveness is thoroughly investigated. Here, we evaluated a total of 23 commercial reagents designed for clinical sample transportation, nucleic acid extraction, and virus inactivation for their ability to inactivate SARS-CoV-2, as well as seven other common chemicals, including detergents and fixatives. As part of this study, we have also tested five filtration matrices for their effectiveness at removing the cytotoxic elements of each reagent, permitting accurate determination of levels of infectious virus remaining following treatment. In addition to providing critical data informing inactivation methods and risk assessments for diagnostic and research laboratories working with SARS-CoV-2, these data provide a framework for other laboratories to validate their inactivation processes and to guide similar studies for other pathogens.